PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA NEGERI 4 PADANG - Firda, Winda (Departemen Matematika, 2023)
The basic skills that students must master are communication skills. However, class XI MIPA students at SMAN 4 Padang are still lacking in mathematical communication. Model problem based learning (PBL) is used to overcome this problem. Descriptive research and quasi-experimental research (quasi experiment) with plans Nonequivalent Postest-only control group design use in this research. The research population is class XI MIPA students at SMAN 4 Padang. Sample classes are taken through engineering simple random sampling. The instruments used are quizzes and final tests. Hypothesis test results, then reject. Thus, students learn with models PBL have better mathematical communication skills compared to students who learn using the direct learning modelKeywords– Problem Based Learning Model, Mathematical Communication Skills, Direct Learning